Association of Category of Cattle Exposure with Tuberculosis Knowledge among Dairy Workers in Bailey County, Texas. Issue 3 (3rd July 2021) - Rodriguez, Anabel; Douphrate, David I.; Gimeno Ruiz de Porras, David; Perez, Adriana; Hagevoort, Robert; Nonnenmann, Matthew; Cienega, Leeroy
ABSTRACT: Objective: To determine the knowledge of tuberculosis (TB) among dairy workers in Bailey County, Texas. Methods: A cross-sectional study design was used to collect 225 survey responses concerning knowledge of TB among dairy workers on 10 dairy farms in Bailey County, Texas. Subjects used iPad tablets to log responses to 15 demographic questions and a 17-item TB knowledge quiz, measured by: (1) TB characteristics, (2) TB transmission, (3) TB symptoms, (4) TB diagnosis, (5) TB treatment, and (6) bovine TB. A proxy for exposure, dairy workers were classified into categories of cattle exposure – high, medium, and low. Results: Relative to the medium/low group, workers in the high group tended to be younger (32.6 (SD 11.0)), Guatemalan (52.6%), K'iche' speaking (37.8%), males (89.1%) with less years living in the U.S. (10.8 [SD 12.5]) and lower levels of formal education completed (59.6% with no formal/elementary level). Overall, the average score was 7.1 (SD 4.9) out of 17 (41.8% out of 100.0%). Relative to one another, the medium/low group (8.0 (SD 4.6) out of 17) scored better than the high group (6.7 [SD 5.1] out of 17). No significant associations were found between the category of exposure and TB knowledge score. Conclusion: Deficiencies in TB knowledge were identified in all categories of exposure. TB training on dairy farms should include all measured tested in this study and should be administered to all workers regardless of the category of exposure.